DETERMINASI PEMBIAYAAN MUSYARAKAH - Oktaviyori, Regi; Praptiningsih, Praptiningsih (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2015)
This study aims to examine the determination of musyarakah financing in Bank Syariah Mandiri (BSM) period March 2008-December 2011. The data is obtainedbased on bank finance reporting that at publication. It is gained sample amount of 44 months. The analysis technique used here is multiple linier regression and hypothesis test using t-statistic and F-statistic with level of significance 5%. The result of this research is Third Parties Fund (DPK) and return gives significantly on musyarakah financing. The return on asset is not significant to musyarakah financing. By simultaneous, musyarakah financing give significant influence on the level of Third Parties Fund, return and return on asset.